The use of celebrity endorsement in advertising promotion / Ramli Saad, Wan Shahrul Aziah Wan Mahamad and Yong Azrina Ali Akbar - Saad, Ramli; Wan Mahamad, Wan Shahrul Aziah; Ali Akbar, Yong Azrina (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2022)
Endorsement is a type of advertising in which well-known personalities or celebrities with a high level of public recognition, trust, respect, or awareness are used. In advertising promotional efforts, celebrities such as actors, actresses, comedians, singers, athletes, and many others are employed to advertise products or services. This is due to the celebrity's own fan base, who will purchase the things they endorse. Furthermore, when it comes to aiding a brand or a product during marketing efforts, each celebrity endorser has unique traits and benefits. As a result, the more famous or well-known celebrity endorser is, the more expensive it is to use their image to express a product's or brand message's attractiveness. Popularity is a term coined to describe how well-known people can affect customers' attitudes, perceptions, and intentions. The more well-known the endorser, the greater the influence he may have on the consumer's view of the brand and buying intent (Nguyen, 2021).